The Influence of Job Satisfaction Affecting Organizational Commitment of the Small and Medium Business Employee - Moonsri, Kristiya (Asian Administration and Management Review, 2019)
The purposes of this research were: 1) to study the degree of job satisfaction the small and medium business employee 2) to study the degree of organizational commitment the small and medium business employee 3) to study the correlation coefficient between job satisfaction and organizational commitment of the small and medium business employee 4) to study the influence of job satisfaction affecting organizational commitment of the small and medium business employee. The sampling group was the 550 SME’s employees in Phetchabun province. The tool for data collecting was a five rating scale questionnaires. The statistics used in this research were percentage, mean, standard deviation, pearson correlation coefficient and enter multiple regression analysis. The result shows that the degree of job satisfaction the small and medium business employee is overall found to be high ( x = 3.84). The degree of organizational commitment the small and medium business employee is overall found to be high ( x = 3.75). The level of satisfaction of all elements contains a positive correlation towards the organizational commitment, with a statistic significance value of 0.01. The job satisfaction on individualism has influence on organizational commitment as it carried the value (beta =.386, t = 10.153, p < 0.001). And job satisfaction on work conditions has influence on organizational commitment as it carried the value (beta =.303, t = 7.949, p < 0.001). Both of two variables could predict organizational commitment at 33 percent.